User Acceptance of a Gold Dinar Based Electronic Payment System - Mohd Nazri Muhayiddin; Elsadiq M.A.; Hishamuddin Ismail (2011)
This study is intended to solve a few constraints existed in physical gold dinar when used as a form of payment. One dinar is equal to 4.25 gram of fine gold. Specifically, this work proposes the use of e-commerce technology to solve those constraints. But before the actual system can be implemented, this research seeks to find out whether or not the public would be ready to adopt the concept of an electronic dinar payment system. The research framework is based on Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003). It measures the user acceptance based on these constructs; performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention to use. In addition, anxiety and perceived credibility are added as two new constructs. Data collection is based on a questionnaire survey. From the descriptive analysis results, it is discovered that most of the respondents participated in this survey generally agree with the idea of using the proposed dinar based payment system (mean rating of above 4.00)